2018
DOI: 10.1039/c8ra02560f
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin layered MoS2 nanosheets with rich active sites for enhanced visible light photocatalytic activity

Abstract: Edge-rich active sites of ultrathin layered molybdenum disulphide (MoS2) nanosheets were synthesized by a hydrothermal method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…The degradation of the methylene blue is due to the photocatalytic activity via efficient charge separation in MoS 2 nanosheets having high mobility of charge carriers[35][36][37][38][39][40][41][42]44 . A qualitative comparison of our work with other reported work has been mentioned inTable 1[45][46][47][48][49] .…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…The degradation of the methylene blue is due to the photocatalytic activity via efficient charge separation in MoS 2 nanosheets having high mobility of charge carriers[35][36][37][38][39][40][41][42]44 . A qualitative comparison of our work with other reported work has been mentioned inTable 1[45][46][47][48][49] .…”
mentioning
confidence: 69%
“…Comparison between the photocatalytic performances of MoS 2 nanosheets and other nanostructure in the degradation of methylene blue dye under different light sources[45][46][47][48][49] .…”
mentioning
confidence: 99%
“…12,13 The 1T-MoS 2 phase was found to be a superior catalyst due to the high carrier mobility, higher hydrophilicity and abundant active sites, not only at the edges of the nanosheets but also within the basal plane of the 1T phase. [14][15][16] Recent studies have shown that the 1T and 2H phases coexist in single layers of hybridized MoS 2 (ref. [17][18][19] with 1T-phase concentration up to 70%.…”
Section: Introductionmentioning
confidence: 99%
“…The E 1 2g /A 1 g peaks of defect-rich MoS 2 and bulk MoS 2 are at ∼380.7/406.1 and∼383.0/408.5 cm −1 , respectively. Compared to bulk MoS 2 , the Raman peaks of defect-rich MoS 2 blue-shift, possibly owing to the vacancies in its structure [49]. Furthermore, the broader and weaker Raman peaks of the defect-rich MoS 2 than bulk MoS 2 imply its weak crystalline and abundant defects in its basal plane [50][51][52].…”
Section: Number Ofmentioning
confidence: 99%